2008
DOI: 10.3390/ijms10010037
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Toxicity of Ochratoxin A in Rat Embryo Midbrain Micromass Cultures

Abstract: Embryonic midbrain micromass cultures were exposed for five days to ochratoxin A (OTA) at seven concentrations (ranging from 0.16 to 10 µg/mL). Cell viability was assessed in neutral red uptake test (NRU), and differentiation -by immunoenzymatic determination of structural proteins (β III -tubulin, MAP2, GFAP) expression level as well as by computer image analysis. Dose dependent decrease in cell number and differentiation was observed. Concentration-response curves were analysed and the mean inhibition concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…According to this finding, we found a decrease in the number of GFAP + cells starting from the second dose, consistent with the proliferation BrdU assay. proliferation and differentiation with OTA administration in a dose-dependent manner, which is coherent with previous observations (Sava et al, 2007;Wilk-Zasadna & Minta, 2009;Zhang et al, 2009). Ultrastructural characterization of mice SVZ after OTA treatment.…”
Section: Effect On Cell Differentiationsupporting
confidence: 93%
See 3 more Smart Citations
“…According to this finding, we found a decrease in the number of GFAP + cells starting from the second dose, consistent with the proliferation BrdU assay. proliferation and differentiation with OTA administration in a dose-dependent manner, which is coherent with previous observations (Sava et al, 2007;Wilk-Zasadna & Minta, 2009;Zhang et al, 2009). Ultrastructural characterization of mice SVZ after OTA treatment.…”
Section: Effect On Cell Differentiationsupporting
confidence: 93%
“…Previous works in vitro, determined a negative effect of OTA in terms of viability and proliferation on different cellular types of the CNS such as mesencephalic embryonic cells (Wilk-Zasadna & Minta, 2009), rat and human neurons (Zhang et al, 2009) and NSCs from the adult mouse hippocampus (Sava et al, 2007). We found that the exposure to increasing doses of OTA (0.01-100 μg ml À1 ) caused a progressive decrease in cell proliferation and viability, reflecting an accumulative effect.…”
Section: Negative Effect Of Ochratoxin a Exposure On Brain Developmentmentioning
confidence: 59%
See 2 more Smart Citations
“…Ochratoxin A (OTA) is a mycotoxin that is produced by several fungal species in the Aspergillus and Penicillium genera [1,2,3]. OTA displays nephrotoxicity [4], hepatotoxicity [1], carcinogenicity [5], and neurotoxicity [6] in mammals.…”
Section: Introductionmentioning
confidence: 99%